Eco-Friendly Pretreatment of Cotton Fabric With Banana Ash and Dyeing Using Banana Sap - Dhar, Avik Kumar; Bhattacharjee, Maitry; Rima, Most. Mahfuza; Rashid, Muhammad Abdur (European Scientific Journal, ESJ, 2017)
The aim of this study is to evaluate environment supportive pretreatment and dyeing process. In this project, pretreatment of cotton fabric was done by using banana ash. Also, dyeing was carried out with banana sap along with different mordants that are eco-friendly and cost saving. Here, all the experiments were carried out on woven (plain) fabric of 141 GSM. Firstly, cotton fabric was scoured by means of banana root’s ash (pH-10.2). It was then dyed with banana sap (pH-5.4). This banana ash scoured cotton fabric was compared with conventionally scoured cotton fabric through weight loss % and absorbency test. In addition, fastness properties and performance of dyeing were measured through CIE L*C*h, K/S value, and different color fastness tests. Banana ash scoured and dyed with banana sap, using mordant (horitoky), provided the best dyeing performance and color fastness to wash, rubbing, and perspiration than the others.